ON THE RECEPTION OF GEORG TRAKL’S WORK IN CZECH POETRY - Malý, Radek (Porównania, 2012)
The author of the study examines the relation between the poetry of the Austrian expressionist Georg Trakl (1887–1914) and Czech literature, especially poetry. Trakl‘s work in translations by Bohuslav Reynek has affected the development of the modern Czech poetry. The thirties of the twentieth century in the Czech poetry are marked by pessimism, motifs of death, decay, frustration and fear. Trakl´s poetry translated into Czech was a contributory cause of this atmosphere. We can already find specific and significant manifestations of its influence in the work of Bohuslav Reynek, and in the first two collections of František Halas. In varying degrees, they have left traces in the poetry of František Hrubín, Vilém Závada and Jan Zahradníček. The echoes of Trakl's poetry can also be read in the sixties by poet Zbyněk Hejda.